Diagnosis and Treatment of Multisystem Inflammatory Syndrome Following COVID-19 in Children - Leila Shahbaznejad; Azin Hajialibeig; Mohammad Reza Navaeifar; Zahra Doorandish; Mohammad Sadegh Rezai (Journal of Mazandaran University of Medical Sciences, 2021)
Multisystem Inflammatory Syndrome in Children (MIS-C) is recognized as a life threatening complication of Coronavirus disease (COVID-19) in children which can affect major systems such as cardiovascular, respiratory, blood and coagulation, renal, and nervous system. Mild cases of MIS-C can be followed up closely, but, severe illnesses that require hospitalization or pediatric intensive care are also common. Treatment of these patients includes supportive measures to improve the function of vital organs such as the heart and arteries, respiration, and kidneys. Antiviral therapy is recommended in patients with clear involvement of the respiratory system. Treatment with empirical antibiotics and drugs effective in suppressing or modulating the immune system such as steroids in various doses, intravenous immunoglobulins, biologic drugs, anticoagulants, and antiplatelets are recommended. In case of shock or decreased cardiac function, vasopressor drugs are suggested along with supportive measures to maintain tissue perfusions such as albumin and compressed red blood cells. Timely diagnosis and appropriate treatments improve the patient's condition and evaluation of long-term complications of this disease should be done.